The effect of pH on the corrosion rate of 316L Stainless Steel, Nitinol, and Titanium-6%Aluminum-4% Vanadium in Hank's Solution / Nik Rozlin Nik Masdek ... [et al.] - Nik Masdek, Nik Rozlin; Wahab, Nor'Aini; Ahmad Nawawi, Natasha; Tajudin, Aznul (UiTM Press for the Research Management Center (IRMI), Universiti Teknologi MARA, 2021)
Nowadays, the application of 316L Stainless Steel, Nitinol and Ti-6Al4V alloys as biomaterials have become popular due to their implant performance and durability. In this research work, the effect of pH on the corrosion rate of 316L Stainless Steel, Nitinol and Ti-6Al-4V alloys have been investigated. An electrochemical method was applied to investigate the corrosion behaviour of these biomaterials under simulated biological condition. The potentiodynamic polarisation were performed in a Hank's solution with a pH value of 7.4 (neutral) and 5.2 (acidic). SEM, XRD, microhardness and surface roughness were also carried out to characterise the corroded surface. The potentiodynamic polarisation results showed that both Ti-6Al-4V and 316L stainless steel had high corrosion rate at pH 5.2 (acidic) as compared to pH 7.4 (neutral). The corrosion rate for Ti-6Al-4V alloys was 22.80×10-3 mmpy at pH 7.4 and increased to 23.65×10-3 mmpy at pH 5.2. Similar behaviour was observed for 316L stainless steel where the corrosion rate increasing from 2.387×10-3 mmpy at pH 7.4 to 5.325×10-3 mmpy at pH 5.2. However, different corrosion behaviour was observed for Nitinol as the corrosion rate decreasing from 17.65×10-3mmpy to16.04×10-3 mmpy at pH 7.4 and pH 5.2, respectively. Hence, the decrease in pH value was found to not cause any significant effect on the corrosion resistance of Nitinol as compared to 316L SS and Ti-6Al-4V alloys.